(3GdQb GdefThQ dHjGf eYQGL GdfHj GdefUhQs - (3GdYdhj, GdehShj, GdOGQGHj, GdcTaj(B.(3, LYaQ Hf CHj ESMGb, (B1267 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B...(3deG cGf eYQGL fHjfG Udi Gddg Ydjg hBdg HLSOg GdTQja GdHTQj hLSeg GddWja GdYfUQj aj YGde GdjaXI hGdMS GdXGgQj ef GdHjJ (B...s
(3BNQgG (B:s
.. (3bGd KGfjG EdG Cfg Hcd TjA eMjW haj gPG GdbOQ GdcaGjI hGdgOGjI aEf Gdbdjd jOd Ydi GdcKjQ(B...(3GNJJe GdcdGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1\487s
(3GdPQjYI (B11 - 178 ( 1502 )s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds